Preferences for long‐term follow‐up care in childhood cancer survivors. (23rd August 2016) - Michel, G.; Gianinazzi, M.E.; Eiser, C.; Bergstraesser, E.; Vetsch, J.; von der Weid, N.; Kuehni, C.E.; ,
Abstract : Follow‐up care is important for childhood cancer survivors to facilitate early detection and treatment of late effects. We aimed to describe preferences for different organisational aspects and models of follow‐up care among Swiss childhood cancer survivors, and characteristics associated with preferences for different models. We contacted 720 survivors aged 18+ years, diagnosed with cancer after 1990 (age 0–16 years), registered in the Swiss Childhood Cancer Registry (SCCR), and Swiss resident, who previously participated in a baseline survey. They received questionnaires to assess attendance and preferences for follow‐up (rated on 4‐point scales, 0–3). Clinical information was available from the SCCR. Survivors ( n = 314: response rate 43.6%; 47.8% still attended follow‐up) rated clinical reasons for follow‐up higher than supportive reasons ( p < .001). They rated checking for cancer recurrence (mean = 2.78, SD = 0.53) and knowing about risks for my children most important (mean = 2.22, SD = 0.83). They preferred to attend a children's hospital (mean = 1.94, SD = 1.11), adult hospital (mean = 1.86, SD = 0.98) or general practitioner (mean = 1.86, SD = 1.01) rather than a central specialised late effects clinic (mean = 1.25, SD = 1.06, p < .001), and be seen by paediatric (mean = 2.24, SD = 0.72) or medical oncologist (mean = 2.17, SD = 0.69). Survivors preferred decentralised clinic‐based follow‐up, rather than one central specialised late effects clinic. Survivors' preferences should be considered to ensure future attendance.